ORAL STEREOGNOSITIC ABILITY OF EDENTULOUS PATIENTS BEFORE AND AFTER REHABILITATION WITH COMPLETE DENTURE - Mehwish Urooj; Asma Siddiqui; Abdur Rehman; Mehmood Hussain; Moin Khan; Hina Nafees (Pakistan Oral & Dental Journal, 2022)
To determine mean change in oral stereognostic ability score & duration of time taken for sensory perception of edible objects before & after insertion of complete denture in completely edentulous non-denture wearer. The study was conducted at Department of Prosthodontics, Hamdard University Dental Hospital in Karachi-Pakistan. Thirty Patients were enrolled after explaining the procedure. The test was performed after medical, dental history, clinical examination where the subject was seated in an upright position. Test specimen were made from carrots with the help of nickel chromium punches available in six standardized shapes that are: circular, oval, triangle. Square, star and ellipse. For proportion of patients correctly identifying the shape of objects after denture insertion, there was a drastic improvement seen at one month in comparison to baseline for all shape types. Majority of the patients had improved oral stereognostic ability at one month of denture insertion with a signification p-value in all shape types (
Keywords: Oral stereognostic; edentulous; Removable prosthesis